2004
DOI: 10.1086/423237
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons as a Tracer of Star Formation?

Abstract: Infrared (IR) emission features at 3. 3, 6.2, 7.7, 8.6 and 11.3 µm are generally attributed to IR fluorescence from (mainly) FUV pumped large Polycyclic Aromatic Hydrocarbon (PAH) molecules. As such, these features trace the FUV stellar flux and are thus a measure of star formation. We examined the IR spectral characteristics of Galactic massive star forming regions and of normal and starburst galaxies, as well as AGNs and ULIRGs. The goal of this study is to analyze if PAH features are a good qualitative and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
495
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(520 citation statements)
references
References 63 publications
24
495
1
Order By: Relevance
“…It gives log ( (Figure 4). Similar trends are reported by Peeters et al (2004) and Imanishi et al (2007). In order to check if this is true, we obtain a linear fit to the detections with SB SEDs which are not ULIRGs.…”
Section: The Pah 33 μM Emission As a Star Formation Indicatorsupporting
confidence: 65%
See 1 more Smart Citation
“…It gives log ( (Figure 4). Similar trends are reported by Peeters et al (2004) and Imanishi et al (2007). In order to check if this is true, we obtain a linear fit to the detections with SB SEDs which are not ULIRGs.…”
Section: The Pah 33 μM Emission As a Star Formation Indicatorsupporting
confidence: 65%
“…Recently, Yamada et al (2012) have found that the correlation between L PAH3.3 / L IR and L IR has a break around L IR ∼ 10 12 L from another MP of AKARI, MSAGN. There is another candidate other than AGN activity that may contribute to L IR for ULIRGs: embedded young stellar objects (YSOs; Peeters et al 2004;Spoon et al 2002Spoon et al , 2007. Although embedded YSOs are from star-forming regions, they should be considered as a non-typical star-forming contribution to L IR .…”
Section: The Pah 33 μM Emission As a Star Formation Indicatormentioning
confidence: 99%
“…The PAH features are often used as indicators of the star formation rate (SFR) of galaxies (see e.g. Peeters, Spoon, & Tielens 2004;Wu et al 2005;Diamond-Stanic & Rieke 2012;Esquej et al 2014), together with low ionization potential (IP) MIR emission lines such as [Ne II]λ12.81 µm (Spinoglio & Malkan 1992;Ho & Keto 2007;Pereira-Santaella et al 2010;Spinoglio et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mid-IR spectra of Active Galactic Nuclei (AGN) often display ionic lines and also lack PAH emission features, but the continua are typically even flatter between 5-20 µm than SBS 0335-052 (see ISO observations of Seyfert 1s by Clavel et al 2000, or the nuclear spectrum of NGC 1068 by Sturm et al 2000 andLe Floc'h et al 2001 as well as Peeters et al 2004). If metal poor galaxies such as SBS 0335-052 can be present at z ∼ 0.06, it is likely that similar systems may exist not only as high-z primordial galaxies, but also at intermediate redshifts 0.5 < z < 1.5 where moderate luminosity galaxies (L IR < 10 11 L ) are accessible with the deep infrared surveys performed by Spitzer.…”
mentioning
confidence: 99%